HPLC법을 이용한 효소처리스테비아의 분석법 개선 연구 - 윤소정(Sojeong Yoon); 홍성준(Seong Jun Hong); 조성민(Seong Min Jo); 정향연(Hyangyeon Jeong); 조승목(Suengmok Cho); 이양봉(Yang Bong Lee); 신의철(Eui-Cheol Shin) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2023)
본 연구는 효소처리스테비아 분석법에 대한 개선시험법을 제시하는 연구로써 기존 JECFA에서 제시한 6종의 효소처리스테비아 분석법을 기본으로 하여 13종의 효소처리스테비아의 동시 분석을 진행하였다. 13종의 효소처리스테비아의 분석은 method validation을 통해 타당성을 제시하였고, 서로 다른 세 곳의 분석 기관에서의 동시 분석을 통해 기관별 오차, 분석일차, 그리고 분석자의 차이에 의해서도 타당한 결과를 얻을 수 있었다. 이에 대한 실험을 통해 상업용 효소처리스테비아 제품의 적용을 진행하여 13종 중 11종의 효소처리스테비아 배당체가 정량 및 정성이 이루어졌다. 이에 본 연구에서 제시된 시험법을 근거로 하여 공인된 효소처리스테비아의 정량 및 정성 연구의 체계화가 가능한 것으로 보인다. This study conducted experiments under varied conditions using high performance liquid chromatography (HPLC) to improve the enzymatically modified stevia analysis method presented at the Joint FAO/WHO Expert Committee on Food Additives. The modified method was thereafter applied for the analysis of enzyme-treated stevia. HPLC was equipped with an NH2 column, acetonitrile, and water as the mobile phase, and the flow rate was adjusted to 0.5 mL/min. Each limit of detection and limit of quantitation was analyzed for method validation. Precision and repeatability were also analyzed and were determined to be within the guideline range. Totally, 13 enzymatically modified stevia were separated by HPLC chromatogram. Commercial products were subsequently analyzed using the improved method, and 11 types of enzymatically modified stevia were detected. Our results validate that the improved method can officially be applied for testing enzymatically modified stevia. KCI Citation Count: 0